PENGARUH FUNGI MIKORIZA ARBUSKULA (FMA) DAN MYCORRHIZAL HELPER BACTERIA (MHB) TERHADAP PERTUMBUHAN JABON (Anthocepalus cadamba Roxb.) The Effect of Arbuscula Mycorrhizal Fungi (AMF) and Mycorrhizal Helper Bacteria (MHB) on Growth of Jabon - Hutami Indah Pertiwi; Sri Wilarso Budi R.; Arum Sekar Wulandari (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
Jabon (Anthocepalus cadamba Roxb.) is one of the fast-growing species that naturally spread in some areas of Indonesia. Known as well adapted to some types of soil, and attributes to a quite high of economical prospects value. Interaction of Arbuscular Mycorrhiza Fungi (AMF) symbiotic involve not only between fungi and plant’s root but also involving supporting organisms (bacteria). This bacteria capable to stimulating the development of mycorrhizal hyphae namely as Mycorrhiza Helper Bacteria (MHB). The aims of this research was to discover of bacterial isolates that can stimulate the development of AMF in Jabon seedling and to examine the effectiveness of MHB isolate and AMF toward Jabon growth. The experiment was conducted in Completely Randomized-split splot design with two factors. The main plot was AMF with two levels; without AMF (M0) and with AMF respectively. Bacteria as the sub-plot with 19 levels consist of the control (B0), Isolate of Glomus sp with coding B1, B2, B3, B4, B5, B6, B7, B8, B9, B10, B11, B12, B13, B14, B15, B16, B17, and B18 respectively. Our experiment result showed that AMF inoculated of Jabon seedling had significantly effect on root colonization and root dry weight. The average of root colonization was 20.2%. Root dry weight increased 4.69% compared to control. Bacteria were suspected as MHB has not provided significant resultsKey words: arbuscular mycorrhizal fungi, jabon, mycorrhizal helper bacteria